Pengaruh Dukungan Keluarga terhadap Perilaku Self Management Hipertensi pada Masa Pandemi Covid-19 - Tutik Yuliyanti; Novi Indah Aderita; Surati Ningsih (Jurnal Kesehatan, 2022)
Family support is important to maintain effective behavior in the management of hypertension. The purpose of this study was to analyze the effect of family support on hypertension self-management behavior during the COVID-19 pandemic. This type of research is descriptive analytic with a cross sectional design. The population in this study were hypertensive people who lived with their families. The sampling technique used was purposive sampling with a sample of 100 people. The data analysis technique used was simple linear regression analysis. The results of the study: there is a significant effect between family support on hypertension self-management behavior. Every 1 increase in the family support score will increase the hypertension self-management behavior score by 0.699. The family support variable was able to explain 11.8% of the variations in hypertension self-management behavior, while the rest was explained by other variables not included in this study. Conclusions: family support has an effect on hypertension self-management behavior.